(untitled) (Nepalese Journal of Ophthalmology, 2013)
Background: Solitary neurofibroma in the absence of neurofibromatosis is of rare occurrence and very few cases have been reported till date. Objective: To report a case of a solitary intra-ocular neurofibroma. Case: A 65-year-old man presented to us with a large swelling appearing to arise from right pthisical eye for the past one and a half years. After knowing the extent and origin of mass lesion, right eyeball was enucleated and subjected to histopathological examination which revealed intraocular neurofibroma in the absence of neurofibromatosis which is of very rare occurrence. Conclusion: The isolated neurofibroma of intraocular origin can present as an isolated orbital mass without systemic features. Nepal J Ophthalmol 2013; 5(10): 262-264 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8740